ANALISIS KECEPATAN RATA-RATA KEDALAMAN BERDASARKAN PENGUKURAN KECEPATAN TITIK PADA ALIRAN SERAGAM - , ALIFFIA LOVEMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The measurement of velocity parameter becomes very important in the planning of waterworks. The method which is used for velocity data measurement is a direct measurement methods in the field or laboratory in order to obtain results closer to real conditions. To support the efficiency of time, effort, and cost, it is often the measurements are only done at specific points which have been considered to represent the average velocity of a channel. In this study, an analysis of a number of secondary data includes data on the uniform flow velocity distribution which are clear water flow and the flow with the suspended sediment has been done. Velocity measurement method which are used